The relationship between perceived social support and fear of childbirth in pregnant women: a systematic review and meta-analysis - Zohreh Alizadeh-Dibazari; Mahsa Maghalian; Mojgan Mirghafourvand (BMC Psychology)
Abstract Background Despite being a natural process, childbirth often evokes fear due to its unpredictable nature. This fear can lead to significant emotional distress and various physical and mental health complications. While social support from family, friends, and partners is thought to reduce fear, its effectiveness remains unclear. This systematic review and meta-analysis aims to determine the relationship between fear of childbirth and various sources of social support, including overall support, support from family, friends, and partners. Methods A systematic search was conducted across PubMed, Web of Science, Cochrane, Scopus, SID, and Google Scholar for relevant studies published through November 2024. Study quality was assessed using the Newcastle-Ottawa Scale. Subgroup analyses were performed based on study quality. To determine result robustness, two separate sensitivity analyses were carried out: one in which individual studies were sequentially removed, and another where studies using different assessment tools were excluded. Finally, the influence of maternal age, gestational age, multiparity, and pregnancy planning on outcomes was examined through meta-regression analysis. Results From 1,542 screened studies, 17 were included (n = 5,535 women). Meta-analysis revealed significant inverse correlations between fear of childbirth and both perceived social support (r = -0.23, 95% CI -0.39 to -0.05, 16 studies, 5,435 women; p = 0.01; random-effects model) and partner support (r = -0.29, 95% CI -0.46 to -0.09, 5 studies, 1,254 women; p < 0.01; random-effects model). No significant associations emerged for family (r = -0.12, 95% CI -0.26 to 0.02, 3 studies, 530 women; p = 0.10; random-effects model) or friend support (r = -0.05, 95% CI -0.14 to 0.03, 3 studies, 530 women; p = 0.22; fixed-effects model). Results varied significantly by study quality (p < 0.001) but were unaffected by maternal characteristics in meta-regression. Sensitivity analyses confirmed result stability. Conclusion This meta-analysis suggests that greater social support, particularly from partners, can help alleviate fear of childbirth. However, support from friends and family did not show a clear link to reduced fear. Due to limitations in the quality of the studies reviewed, further high-quality research is needed to draw definitive conclusions.